A Sociolinguistics Role in Teaching English for Tour Guide - I Nengah Laba; I Gusti Ayu Nila Wijayanti (International Journal of Linguistics and Discourse Analytics, 2022)
The developments in the tourism sector has caused the increase of tourism education and training massively in Bali. This has also developed the remarkable advancements in other fields, such as linguistics, sociology and IT. In order to have a more comprehensive understanding of the development of tourism, it is important to consider the contribution of other research areas of research in linguistics and sociolinguistics. The study of the language of tourism has emerged as an ESP. This study aims to analyze the sociolinguistics phenomena in the implementation of teaching English for tour guides. The study employed qualitative method with case study approach. The results of the study show that sociolinguistics has a contribution in language learning. Sociolinguistics as a scientific discipline that studies language in relation to the community factor can provide students with good foundation they need to learn English for tour guides